Analysis of Arab Nahwu Textbooks In The Ta'lim Line of Al-Lughah Al-'Arabiyat li An-Natiqina Bighairiha - Nurul Abidin (Al-Hayat: Journal of Islamic Education, 2018)
Arabic is an international language that can foster unity and affection among Muslims wherever they are. Therefore, this language is widely studied in various educational institutions owned by Muslims. Particularly in the present time, the harmonious relationship between the rising Muslim countries, accompanied by rapid technological developments, encourages Muslims to learn this language in earnest. This paper focuses his analysis on one of the books of the Genealogy of Ta'lim al-Lughah al-Arabiyah, the book of Nahwu. Broadly speaking the concept of writing a book of every book in the genealogy written with the same concept. The election on Nahwu's book is because according to the author's opinion, this book can represent al-mawad al-lughah al-arabiyah (other Arabic lessons) in the series of genealogy books. The analysis of this book covers two aspects: 1. General description of the book; a. The name of the book, b. Author of book, c. Elements of the book, and d. Topics. 2. The subject matter of the book; a. Text of the material and its topics, b. Language, vocabulary, term, c. Learning objectives, d. The topics of Nahwu's rule, e. Teaching methods, f. Teaching media, and g. Exercises.Bahasa Arab adalah bahasa internasional yang dapat menumbuhkan persatuan dan kasih sayang di antara Muslim dimanapun mereka berada. Karena itu, bahasa ini banyak dipelajari di berbagai lembaga pendidikan yang dimiliki oleh umat Islam. Khususnya di masa sekarang, hubungan harmonis antara negara-negara Muslim yang sedang berkembang, disertai dengan perkembangan teknologi yang pesat, mendorong umat Islam untuk belajar bahasa ini dengan sungguh-sungguh. Naskah ini memfokuskan analisisnya pada salah satu buku dari Silsilah Ta'lim al-Lughah al-Arabiyah, buku Nahwu. Secara garis besar konsep penulisan buku setiap buku dalam silsilah ditulis dengan konsep yang sama. Pemilihan pada buku Nahwu adalah karena menurut pendapat penulis, buku ini dapat mewakili al-mawad al-lughah al-arabiyah (pelajaran bahasa Arab lainnya) dalam seri buku silsilah. Analisis buku ini mencakup dua aspek: 1. Gambaran umum buku, b. Penulis buku, c. Elemen buku, dan d. Topik. 2. Subjek buku: teks materi dan topiknya, b. Bahasa, kosakata, istilah, c. Tujuan pembelajaran, d. Topik-topik aturan Nahwu, e. Metode pengajaran, f. Media pengajaran, dan g. Latihan.